SHADECO: A low-cost shadow-ring for diffuse measures: State of the art, principles, design and application. (March 2018) - Malet-Damour, Bruno; Guichard, Stéphane; Jean, Aurélien P.; Miranville, Frédéric; Boyer, Harry
Abstract: Nowadays, given the high cost of an experimental phase and to validate the developed models, the calculator is used by more and more researchers. However, experimentation is a major step to validate any model. To get some accurate data, the devices must be efficient. That is why their prices is very expensive. To overcome this problem, researchers leading to new approaches for developing their own prototypes. The challenge is to have accuracy devices for a lower cost. Measurement of diffuse illuminance requires the use of a device to mask the solar disk, like the shadow-ring. In this paper, a manufacturing protocol is proposed to design a shadow-ring, named SHADECO, according to the latitude of the study site and composed of basic materials. For the same efficiency, it allows a cost 4 to 6 times lower than industrial ring. To demonstrate the low cost-saving ratio of the data obtains, a study was conducted on predictive modeling of the behavior of an indoor lighting device. Two models are compared: one using diffuse illuminance deduced (from kt ) and the other using the diffuse illuminance obtained with SHADECO. Using data measured instead of data deduced can improve by almost 34% the model's accuracy. Highlights: State of the art on shadow-band technologies and correction factor. Manufacturing protocol for a low-cost shadow-ring.